(untitled) (Journal of Engineering, 2009)
A new method for generation and simulation of meshing for involute helical gears is presented. The approaches proposed for generation are based on the imaginary application of two rack-cutters one for pinion and the other for gear generation. The proposed simulation of meshing of aligned and misaligned helical gears gives (i) the shift of the bearing contact (real contact path) on pinion and gear tooth surfaces, (ii) the function of transmission errors.